The Influence of Brand Image and Promotion on Product Purchase Decisions Smartphone Samsung Brand at Gion Cell West Bandung Store - Iwan Ernawan Astamoen; Asep Hermawan (International Journal of Integrative Sciences, 2023)
This research is quantitative research at the Gion Cell Store in West Bandung. Researchers determined several concepts, namely brand image and promotion as independent variables, and purchasing decisions as the dependent variable. The sample in this study was 85 respondents, using the methodPurposive Sampling which aims to obtain information that is relevant and available only from certain groups. Hypothesis testing shows that promotional variables and brand image have a positive effect on purchasing decisions. This is indicated by the obtained t count for all variables greater than the t table 1.989318557. Meanwhile, for the F test, the calculated F is greater than the F table 3.107891302. The results of this research show that promotion and brand image have a significant influence on purchasing decisions with an influence of 96.8%